The impact of coarse aggregate mineral compositions on skid resistance performance of asphalt pavement: A comprehensive study. - Chen Zhang; Lihao Zeng; Huimin Wang; Xin Qu (PLoS ONE)
This study aimed to investigate the influence of different coarse aggregate mineral compositions on the skid resistance performance of asphalt pavement. The imprint method was utilized to assess the contact probability between various graded asphalt surface aggregates and tires. Additionally, macroscopic adhesive friction coefficients between polished surfaces of three types of rock slabs (basalt, limestone, granite) and rubber were determined using a pendulum friction tester. Molecular dynamics simulations were employed to model the main aggregate minerals and rubber, and a "sandwich" type constrained shear model was constructed to evaluate micro-scale adhesive friction coefficients. Results indicated a 40% contact probability between aggregate and tire in a unit area of the road surface, highlighting the importance of studying adhesive friction between minerals and rubber. Macroscopically, basalt exhibited the highest adhesive friction coefficient, followed by limestone and granite. At the molecular level, feldspar showed the highest micro-scale friction coefficient with rubber, while quartz exhibited the lowest. The micro-scale adhesive friction coefficients correlated well with the macroscopic findings (correlation coefficient of 0.81), providing theoretical support for optimizing coarse aggregate selection to enhance skid resistance in road applications.